N-alkylated / sulfonated benzimidazole polyaryletherketone / sulphone with controllable grafting density as well as preparation method and application of N-alkylated / sulfonated benzimidazole polyaryletherketone / sulphone

By grafting alkyl/sulfonic acid groups onto the benzimidazole structure and adjusting the monomer molar ratio, the problem of controlling the grafting group ratio was solved, the thermal stability and mechanical properties of the polymer were improved, and the preparation of N-alkylated/sulfonated benzimidazole polyarylether ketone/sulfone with controllable grafting density was realized, which is suitable for alcohol-water separation.

CN121609674APending Publication Date: 2026-03-06ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511540064.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-27
Publication Date
2026-03-06

AI Technical Summary

Technical Problem

Existing technologies make it difficult to precisely control the proportion of grafted groups, and cross-linking reactions may occur between polymer chains during the modification process, affecting grafting efficiency and the accuracy of group distribution, resulting in structural instability of the polymer at high temperatures.

Method used

By grafting alkyl/sulfonic acid groups onto the -NH group of the benzimidazole structure, steric hindrance is provided to avoid cross-linking, and N-alkylated/sulfonated benzimidazole polyarylether ketone/sulfone with controllable grafting density is prepared by adjusting the monomer molar ratio.

Benefits of technology

This technology enables controllable grafting density in polymers, improves the thermal stability and mechanical properties of polymers, avoids gelation, and enhances membrane separation efficiency and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses N-alkylated / sulfonated benzimidazole polyaryletherketone / polyaryletherketone sulfone with controllable grafting density as well as a preparation method and application of the N-alkylated / sulfonated benzimidazole polyaryletherketone / polyaryletherketone sulfone. The preparation method comprises the following steps: firstly, introducing a protecting group on a phenolic hydroxyl group of a bisphenol monomer containing a benzimidazole structure, then carrying out nucleophilic substitution reaction on alkyl halide / alkyl halide sulfonic acid and-NH, and then removing the protecting group to obtain an N-alkylated / sulfonated benzimidazole functionalized bisphenol monomer; copolymerizing the monomer, a bisphenol monomer and a difluoro monomer to obtain a polymer; alkyl or alkyl sulfonic acid is introduced to a benzimidazole ring, so that-NH bonds are passivated, a steric hindrance effect is formed, and gelation of the polymer under a high polymerization degree is avoided; by adjusting the molar ratio of the monomers, the retention stability of the functional groups can be effectively controlled, and compared with the traditional grafting on the polymer, the non-regulation of functionalization and the gelation of the polymer are effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials, and in particular to an N-alkylated / sulfonated benzimidazole polyarylether ketone / sulfone with controllable grafting density, its preparation method, and its application. Background Technology

[0002] To develop green and sustainable renewable energy, ethanol is widely used in various fields such as chemical engineering, defense, and medicine due to its low cost and environmental friendliness. However, ethanol production often involves the addition of a large amount of water, making alcohol-water separation a hotly debated topic. Pervaporation, as a membrane separation technology, can overcome the limitations of gas-liquid equilibrium, offering advantages such as low pollution and high separation efficiency. High-performance pervaporation membranes must possess high stability, high mechanical strength, and high selectivity.

[0003] Polyaryletherketones / sulfones (PBIs) are a class of aromatic polymers containing ether and ketone / sulfone bonds. Their molecular structure contains a rigid benzene ring, thus exhibiting good mechanical properties and chemical resistance. The ether bonds in the molecular structure also provide flexibility, allowing for molding and processing under certain conditions. They are used in aerospace, automotive, and medical device industries. To meet the ever-increasing demands of these fields, high thermal stability, high mechanical properties, and excellent electrical properties have become universally sought-after. Extensive research on PBI modification has shown that introducing specific groups into the polymer backbone or branches can alter its heat resistance, solvent resistance, and electrical properties. Polybenzimidazole (PBI) is a class of heterocyclic polymers containing repeating benzimazole units in its backbone. Its molecular backbone has a ladder-like structure, and the benzene ring and benzimazole in the backbone exhibit strong rigidity. The NH groups on the imidazole ring form intermolecular hydrogen bonds. The high rigidity of the PBI molecular chain and the intramolecular interactions give it excellent heat resistance. Polybenzimidazole (PBI) is typically synthesized by the condensation and cyclization of aromatic tetraamines and diphenyl phthalate (DPI). During polymerization, the multifunctional groups readily form intermolecular forces, leading to gel formation. Therefore, researchers have sought to address this issue and improve polymer properties by grafting PBI. Currently, many studies employ direct grafting methods. However, this method struggles to precisely control the proportion of grafted groups, and cross-linking reactions may occur between polymer chains during modification, further impacting grafting efficiency and the accuracy of group distribution.

[0004] In previous work, Liao JB et al. (Journal of Power Sources, 2015, 285:241-247) prepared a bisphenol monomer containing a benzimidazole structure, and then introduced the benzimidazole structure into the main chain of polyaryletherketone / sulfone via monomer polymerization. However, in an oxidizing environment, the -NH bonds on the benzimidazole ring are easily attacked, affecting the stability of the polymer main chain. Therefore, W. Jin et al. (Materials Today Communications, 2019, 21) improved the polymer structure and synthesized a novel crosslinkable polyaryletherketone. This polymer has adjustable amounts of pendant benzimidazole groups in its side chains. The crosslinking network with benzimidazole groups as crosslinking nodes greatly enhances the thermal stability and mechanical properties of the membrane. Introducing the benzimidazole structure into the polymer side chains creates hydrogen bonding forces between polymer molecules. Appropriate crosslinking helps the molecular chains to align, enhances polymer flexibility, gives the polymer a wider processing range, and improves mechanical properties, thermal stability, and electrical properties. However, during polymerization at high temperatures, the -NH bonds on the benzimidazole ring readily form intramolecular or intermolecular hydrogen bonds with hydroxyl groups, disrupting the original chain structure and leading to crosslinking and the formation of a network structure. This results in uneven distribution of crosslinks and stress, causing the polymer to aggregate and form a gel. In this invention, during the synthesis of benzimidazole-functionalized bisphenols, alkane or sulfonic acid groups are grafted onto the -NH groups, passivating the original structure. Using this monomer as one of the raw materials, the molar ratio of monomers can be arbitrarily controlled to prepare a polymer with controllable grafting density, which can be applied in the field of pervaporation. Summary of the Invention

[0005] This invention starts with molecular structure design and proposes a polymer (N-alkylated / sulfonated benzimidazole polyarylether ketone / sulfone) with controllable grafting density, its preparation method and application.

[0006] This invention uses bisphenol monomers containing benzimidazole structures as raw materials. Alkyl / sulfonic acid groups are introduced onto the -NH group of the benzimidazole structure, passivating the original structure and providing steric hindrance during polymerization, thereby preventing the formation of insoluble substances. By first grafting onto the monomer and then arbitrarily controlling the monomer molar ratio, this invention can effectively regulate the content of N-alkylated / sulfonated benzimidazole in the polymer, achieving controllable grafting density.

[0007] The technical solution of the present invention is as follows: An N-alkylated / sulfonated benzimidazole-functionalized bisphenol monomer has the following structural formula:

[0008] in, R is -(CH2) m CH3 or -(CH2)n SO3 - M + m = 0, 1, or 2, n = 2, 3, or 4, M + for Na + or H + .

[0009] The method for preparing N-alkylated / sulfonated benzimidazole-functionalized bisphenol monomers of the present invention is as follows: Starting with a bisphenol monomer containing a benzimidazole structure, a protecting group is first introduced onto the phenolic hydroxyl group to obtain the protected monomer. The protected monomer, halogenated product, strong base, and anhydrous solvent are mixed and reacted in an ice-water bath for 1-2 hours, followed by reaction at room temperature for 12-24 hours. The reaction solution is then quenched with ice water, extracted with ethyl acetate, and the organic phase is washed with saturated brine, dried with a drying agent (anhydrous sodium sulfate or anhydrous magnesium sulfate), and the solvent is removed by rotary evaporation. The resulting product is then deprotected to obtain an N-alkylated / sulfonated benzimidazole functionalized bisphenol monomer. in, The structural formula of the starting material, a bisphenol monomer containing a benzimidazole structure, is as follows:

[0010] The protecting group of the phenolic hydroxyl group can be benzyl, methyl, or silyl ether, with benzyl being preferred; The halogenated product is a haloalkane or a haloalkylsulfonic acid; the haloalkane is selected from bromoethane, iodomethane, or chloropropane; the haloalkylsulfonic acid is selected from 3-bromopropanesulfonic acid, 2-chloroethanesulfonic acid, or 4-chlorobutanesulfonic acid. The strong base is selected from sodium hydride, triethylamine, or sodium hydroxide; The molar ratio of the protected monomer, halogenated product, and strong base is 1:2.0~2.5:2.0~4.2; The anhydrous solvent is selected from anhydrous tetrahydrofuran or anhydrous N,N-dimethylformamide.

[0011] An N-alkylated / sulfonated benzimidazole polyarylether ketone / sulfone with controllable grafting density was prepared by the following method: Under inert gas protection, the N-alkylated / sulfonated benzimidazole functionalized bisphenol monomer, difluoro monomer, and bisphenol monomer of the present invention are mixed, and an alkaline substance is used as a catalyst and toluene is used as a dehydrating agent. The mixture is reacted in an aprotic polar organic solvent at 150~260°C for 12~36h. After post-treatment, N-alkylated / sulfonated benzimidazole polyarylether ketone / sulfone is obtained. The difluoro monomer is selected from 4,4'-difluorobenzophenone or 4,4'-difluorodiphenyl sulfone; The bisphenol monomer is selected from bisphenol A, hexafluorobisphenol A, bisphenol S or tert-butylhydroquinone; By adjusting the molar ratio of N-alkylated / sulfonated benzimidazole-functionalized bisphenol monomer, difluoro monomer, and bisphenol monomer, the grafting density can be controlled. Preferably, the molar ratio of N-alkylated / sulfonated benzimidazole-functionalized bisphenol monomer to bisphenol monomer is 1:0~10, and the molar ratio of the total N-alkylated / sulfonated benzimidazole-functionalized bisphenol monomer and bisphenol monomer to difluoro monomer is 1:1~2. The alkaline substance is selected from anhydrous potassium carbonate or anhydrous sodium carbonate; The aprotic polar organic solvent is selected from N,N-dimethylformamide, N,N-dimethylacetamide, sulfolane, or N-methylpyrrolidone.

[0012] The N-alkylated / sulfonated benzimidazole polyarylether ketone / sulfone grafts of the present invention, with controllable graft density, can be prepared into pervaporation membranes by solution casting for alcohol-water separation.

[0013] The test method for pervaporation is as follows: cut the membrane into a 3cm diameter circle and place it in the membrane cell, according to the attached... Figure 5 The apparatus was set up with 99% ethanol as the feed solution. The feed solution was first heated to 50°C, and the peristaltic pump was used to circulate the solution for 30 minutes at a flow rate of 50 mL / min. The vacuum pump was then turned on and the pressure controlled at 0.1 MPa. After 6 hours of operation, the test was completed, the mass of the permeate was recorded, and its composition was analyzed by gas chromatography. The formulas for calculating the permeate flux and separation factor are as follows:

[0014] In the formula, J is the permeate flux, m is the mass of the permeate, A is the effective membrane area, and t is the operating time; α A / B Y is the separation factor. A Y B X represents the mass fraction of water and ethanol in the permeate, respectively. A X B These represent the mass fractions of water and ethanol in the raw materials, respectively.

[0015] The beneficial effects of this invention are as follows: 1. This invention provides a polymer with controllable grafting density, its preparation method, and its applications. The polymer of this invention contains both a polyarylether ketone / sulfone structure and an N-alkylated / sulfonated benzimidazole structure, retaining the excellent properties of polyarylether ketone / sulfone while possessing the excellent chemical stability of benzimidazole. By grafting alkyl / sulfonic acid groups onto the -NH group of the benzimidazole structure, a steric hindrance effect is generated during polymerization, providing free volume and effectively preventing cross-linking between the -NH bond and the hydroxyl group, thereby inhibiting the formation of a network structure and avoiding polymer gelation.

[0016] 2. Unlike traditional grafting onto polymers, this invention first modifies the monomers, and then, by controlling the molar ratio of the monomers, can effectively regulate the content of N-alkylated / sulfonated benzimidazole in the polymer, greatly improving the controllability of the polymerization. Attached Figure Description

[0017] Figure 1 NMR spectrum of N-ethylbenzimidazole-functionalized bisphenol prepared in Example 1.

[0018] Figure 2 NMR spectrum of N-propanesulfonic acid benzimidazole-functionalized bisphenol prepared in Example 2.

[0019] Figure 3 NMR spectrum of N-propylbenzimidazole-functionalized bisphenol prepared in Example 3.

[0020] Figure 4 XRD curves of the polymers prepared in Examples 1-6.

[0021] Figure 5 Simplified flowchart of pervaporation test process. Detailed Implementation

[0022] The present invention is further described below through specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0023] In the following examples, the starting material, a bisphenol monomer containing a benzimidazole structure, was synthesized according to the journal article "Sulfonated polyaryletherketone with pendant benzimidazole groups for proton exchange membranes" (Journal of Membrane Science, 2020, 597: 117626). The structural formula of the bisphenol monomer containing the benzimidazole structure is as follows:

[0024] The method for determining the intrinsic viscosity of polymers according to the present invention is as follows: Dissolve an appropriate amount of polymer in DMAC to prepare a solution with a concentration of 0.5 g·dL. -1 The intrinsic viscosity of the solution was measured using an Ubbelohde viscometer at 25°C. The formula for calculating intrinsic viscosity is as follows:

[0025] In the formula, inh The intrinsic viscosity of the polymer is represented by t, the time required for the polymer solution to flow through the capillary is represented by t0, the time required for the pure solvent to flow through the capillary is represented by C, and the concentration of the polymer is represented by C.

[0026] This invention uses differential scanning calorimetry to determine the glass transition temperature of polymers, and the method is as follows: Take 5-10 mg of sample, heat at a rate of 10°C / min under a nitrogen atmosphere, set three temperature programs, and take the value of the third program.

[0027] This invention characterizes the crystalline state of polymers using X-ray diffraction, which follows the Bragg equation:

[0028] In the formula, d represents the interplanar spacing, θ represents the diffraction angle, n is an integer, and λ is the wavelength of the X-ray.

[0029] Example 1

[0030] Bisphenol monomer containing a benzimidazole structure (8.64 g, 20 mmol), benzyl bromide (6.84 g, 40 mmol), anhydrous potassium carbonate (13.80 g, 100 mmol), and 100 mL of acetone were added to a three-necked flask and refluxed at 56°C for 8 h. After the reaction was completed, the reaction solution was poured into a 500 mL beaker containing ice water, filtered through a Buchner funnel, and the filter cake was washed three times with deionized water. The product was dried in a 40°C oven for 12 h and then in a 40°C vacuum oven for 24 h to obtain product P1, with the following structural formula: P1 Product P1 (6.12 g, 10 mmol), bromoethane (2.18 g, 20 mmol), and sodium hydride (0.48 g, 20 mmol) were reacted in 50 mL of anhydrous tetrahydrofuran in an ice-water bath at 0°C for 1 h. The ice-water bath was removed, and the reaction continued at room temperature for 12 h. After the reaction was complete, the reaction mixture was slowly added dropwise to a beaker containing ice water while continuously stirring. The quenched mixture was transferred to a separatory funnel, and the aqueous phase was extracted three times with ethyl acetate. The organic phase was washed with saturated brine, and 7.10 g of anhydrous sodium sulfate was added and stirred for 15 min. The mixture was filtered through a funnel lined with cotton to remove the drying agent. The dried product was transferred to a dropper flask, concentrated under reduced pressure in a rotary evaporator at 30°C, and dried to obtain the protected product P2, with the following structural formula: P2 Product P2 (6.68 g, 10 mmol) was dissolved in 25 mL of ethyl acetate, and 1.35 g of palladium catalyst on carbon was added. The air in the reaction system was purged using a vacuum pump, and hydrogen was introduced three times. A hydrogen-filled balloon was then connected to the reaction system to provide a hydrogen atmosphere, and the reaction was carried out at room temperature for 12 h. After the reaction was complete, the palladium catalyst on carbon was removed by filtration. The filtrate was collected in a dropper bottle and concentrated under reduced pressure using a rotary evaporator. After drying, product P3, namely N-ethylbenzimidazole-functionalized bisphenol, was obtained, with the following structural formula: P3 5 mg of N-ethylbenzimidazole-functionalized bisphenol was dissolved in 0.55 mL of deuterated dimethyl sulfoxide. The structure of the monomer was characterized using an AVANCE NEO 400 nuclear magnetic resonance spectrometer. The results are as follows: Figure 1 shown. δ 10.93 (s, 2H), δ 7.50-7.68 (m, 6H), δ 7.23-7.32 (d, 4H), δ 6.98-7.01 (m, 4H), δ 3.94-3.96 (t, 2H), δ 3.79-3.83 (q, 4H), δ 1.25-1.28 (t, 6H).

[0031] 4,4'-Difluorobenzophenone (1.09 g, 5.0 mmol), N-ethylbenzimidazole-functionalized bisphenol (0.24 g, 0.5 mmol), hexafluorobisphenol A (1.51 g, 4.5 mmol), anhydrous potassium carbonate (1.52 g, 11 mmol), and 40 mL of N,N-dimethylacetamide were added to a three-necked flask. 30 mL of toluene was added to a Dean-Stark water separator. A thermometer, magnetic stirrer, and nitrogen purging tube were connected. After purging with nitrogen for 30 min, the mixture was heated to 150°C and refluxed for approximately 5 h. The temperature was then gradually increased to 170°C, during which water and toluene were removed. The reaction was carried out at 170°C for 12 hours. After the reaction solution cooled, it was slowly added to 500 mL of deionized water. The precipitate was allowed to stand for 2 hours and then filtered. It was then washed three times alternately with hot deionized water at 40°C and hot ethanol at 40°C. Finally, it was vacuum dried at 120°C to constant weight to obtain the polymer, namely, N-ethylbenzimidazole polyarylether ketone with side chains. Its intrinsic viscosity was 1.08 dL / g, and its glass transition temperature (Tg) was 169.5°C.

[0032] Example 2

[0033] The product P1 (6.12 g, 10 mmol), 3-bromopropanesulfonic acid (5.63 g, 25 mmol), and sodium hydroxide (1.68 g, 42 mmol) from Example 1 were reacted in 50 mL of anhydrous DMF in an ice-water bath at 0°C for 2 h. The ice-water bath was then removed, and the temperature was raised to 80°C for another 24 h. After the reaction was complete, the reaction mixture was slowly added dropwise to a beaker containing ice water while continuously stirring. The quenched mixture was transferred to a separatory funnel, and the aqueous phase was extracted three times with ethyl acetate. The organic phase was washed with saturated brine, and 7.10 g of anhydrous sodium sulfate was added and stirred for 15 min. The mixture was then filtered through a funnel lined with cotton to remove the drying agent. The dried product was transferred to a dropper flask, and concentrated under reduced pressure in a rotary evaporator at 40°C. After drying, the protected product P4 was obtained. Deprotection was performed in the same manner as in Example 1, yielding product P5, namely N-propanesulfonic acid benzimidazole-functionalized bisphenol. The structural formulas of P4 and P5 are as follows: P4 P5 The NMR spectrum of N-propanesulfonic acid benzimidazole-functionalized bisphenol is shown below. Figure 2 As shown, where δ 10.67 (s, 2H), δ 9.03 (s, 2H), δ 7.63-7.85 (m, 6H), δ 7.26-7.43 (d, 4H), δ 7.04-7.12 (m, 4H), δ 4.14 (s, 2H), δ 3.78-3.84 (t, 4H), δ 3.28-3.32 (t, 4H), δ 2.73-2.80 (Quintet, 4H).

[0034] 4,4'-Difluorobenzophenone (1.09 g, 5.0 mmol), benzimidazole-functionalized bisphenol N-propanesulfonic acid (0.91 g, 1.5 mmol), bisphenol A (0.80 g, 3.5 mmol), anhydrous potassium carbonate (1.52 g, 11 mmol), and 30 mL of N,N-dimethylacetamide were added to a three-necked flask. 30 mL of toluene was added to a Dean-Stark water separator. A thermometer, magnetic stirrer, and nitrogen inlet were connected, and the reaction was carried out at 170 °C for 28 h. Post-treatment yielded a polyarylether ketone containing benzimidazole propanesulfonic acid in the side chain, with an intrinsic viscosity of 1.63 dL / g, a glass transition temperature (Tg) of 163.5 °C, and a degree of sulfonation of 28.2%.

[0035] Example 3

[0036] The product P1 (6.12 g, 10 mmol), chloropropane (1.57 g, 20 mmol), and sodium hydride (0.53 g, 22 mmol) from Example 1 were reacted in anhydrous tetrahydrofuran as solvent in an ice-water bath at 0°C for 2 h. After removing the ice-water bath, the reaction was continued at room temperature for 16 h. After treatment, P6 was obtained. Deprotection was performed in the same manner as in Example 1 to obtain P7, namely N-propylbenzimidazole-functionalized bisphenol. The structural formulas of P6 and P7 are as follows: P6 P7 The NMR results for N-propylbenzimidazole-functionalized bisphenols are attached. Figure 3 As shown, where δ 10.41 (s, 2H), δ 7.78-7.87 (m, 6H), δ 7.43-7.46 (d, 4H), δ 7.09-7.15 (m, 4H), δ 4.33-3.67 (t, 4H), δ 3.83 (s, 2H), δ 1.82-1.96 (Sextet, 4H), δ 0.87-0.91 (t, 6H).

[0037] 4,4'-Difluorobenzophenone (1.09 g, 5.0 mmol), N-propylbenzimidazole-functionalized bisphenol (2.51 g, 5.0 mmol), anhydrous sodium carbonate (1.17 g, 11 mmol), and 50 mL of N,N-dimethylacetamide were added to a three-necked flask. 30 mL of toluene was added to a Dean-Stark water separator. A thermometer, magnetic stirrer, and nitrogen purging tube were connected, and the reaction was carried out at 170 °C for 36 h. Post-treatment yielded a polyarylether ketone with N-ethylbenzimidazole side chains. The polymer had an intrinsic viscosity of 0.76 dL / g and a glass transition temperature (Tg) of 161.2 °C.

[0038] Example 4

[0039] The method and steps were the same as in Example 1, except that the amounts of bisphenol A and N-ethylbenzimidazole functionalized bisphenol were changed to 0.57 g and 1.22 g, respectively. The resulting polymer had a viscosity of 0.87 dL / g and a glass transition temperature (Tg) of 184.3°C.

[0040] Example 5

[0041] The method and steps were the same as in Example 1. The amounts of 4,4'-difluorobenzophenone, hexafluorobisphenol A, and N-propanesulfonic acid benzimidazole functionalized bisphenol were 2.18 g, 3.02 g, and 0.604 g, respectively. The resulting polymer had an intrinsic viscosity of 1.63 dL / g, a glass transition temperature (Tg) of 163.5°C, and a degree of sulfonation of 28.2%.

[0042] Example 6

[0043] 4,4'-Difluorodiphenyl sulfone (1.27 g, 5 mmol), N-ethylbenzimidazole-functionalized bisphenol (0.24 g, 0.5 mmol), hexafluorobisphenol A (1.51 g, 4.5 mmol), anhydrous potassium carbonate (1.52 g, 11 mmol), and 50 mL of dimethylpyrrolidone were added to a three-necked flask. 30 mL of toluene was added to a Dean-Stark water separator. A thermometer, magnetic stirrer, and nitrogen purging tube were connected. After purging with nitrogen for 30 min, the mixture was heated to 150°C and refluxed for approximately 5 h. The temperature was then gradually increased to 260°C, during which water and toluene were removed. The reaction was carried out at 260°C for 24 hours. After the reaction solution cooled, it was slowly added to 500 mL of deionized water. The precipitate was allowed to stand for 2 hours, filtered, and then washed three times alternately with hot deionized water at 40°C and hot ethanol at 40°C. Finally, it was vacuum dried at 120°C to constant weight to obtain the polymer, namely N-ethylbenzimidazole polyethersulfone with side chains. Its intrinsic viscosity is 1.11 dL / g, and its glass transition temperature (Tg) is 246.6°C.

[0044] Application examples

[0045] The polymers prepared in Examples 1 and 2 were used to prepare films by solution casting. A 5% solids solution was prepared with N,N-dimethylacetamide and cast into a 10-layer substrate. In a glass mold of 10, the solvent is dried. The membrane is cut into 3cm diameter circles and placed in the membrane pool. Through the attachment... Figure 5 The apparatus was set up with 99% ethanol as the feed solution. The feed solution was first heated to 50°C, and the peristaltic pump was used to circulate the solution for 30 minutes at a flow rate of 50 mL / min. The vacuum pump was then turned on and the pressure was controlled at 0.1 MPa. After running for 6 hours, the test was completed, the mass of the permeate was recorded, and the composition was analyzed by gas chromatography.

[0046] The permeation flux and separation factor in Example 1 were 28.36 g / (m²). 2 The permeation flux and separation factor of Example 2 were 76.13 g / (m²) and 11.061, respectively. 2 ·h) and 8.13, compared to polydimethylsiloxane (Xu Youyi, Xu Zhikang. Polymer Membrane Materials, Chemical Industry Press, 2005: 375-415) with a permeation flux of 12.7 g / (m 2 The separation factor (h) and separation factor (8.4) were improved. Membranes prepared from the resulting polymer were able to separate ethanol and water; the polymer with sulfonic acid groups promoted permeation, thus making it suitable for pervaporation.

[0047] The above embodiments demonstrate that the present invention successfully prepared N-alkylated / sulfonated benzimidazole functionalized bisphenol monomers. Furthermore, the polymers obtained by controlling the molar ratio of the monomers all exhibit intrinsic viscosities below 2 dL / g and good thermal stability. The dispersed diffraction peaks observed in the polymer X-ray diffraction patterns indicate that they are all amorphous copolymers with significant steric hindrance. Therefore, the method of the present invention for preparing polymers with controllable grafting density is effective and feasible.

[0048] The above embodiments are used to explain and illustrate the present invention, but not to limit the present invention. Any modifications and changes made to the present invention within the spirit and scope of the claims shall fall within the protection scope of the present invention.

Claims

1. An N-alkylated / sulfonated benzimidazole functionalized bisphenol monomer, having the following structure: wherein, R1 is a C1-C6 alkyl group; R2 is a C1-C6 alkyl group; R3 is a C1-C6 alkyl group; R4 is a C1-C6 alkyl group; R5 is a C1-C6 alkyl group; R6 is a C1-C6 alkyl group; R7 is a C1-C6 alkyl group; R8 is a C1-C6 alkyl group; R9 is a C1-C6 alkyl group; R10 is a C1-C6 alkyl group; R11 is a C1-C6 alkyl group; R12 is a C1-C6 alkyl group; R13 is a C1-C6 alkyl group; R14 is a C1-C6 alkyl group; R15 is a C1-C6 alkyl group; R16 is a C1-C6 alkyl group; R17 is a C1-C6 alkyl group; R18 is a C1-C6 alkyl group; R19 is a C1-C6 alkyl group; R20 is a C1-C6 alkyl group; R21 is a C1-C6 alkyl group; R22 is a C1-C6 alkyl group; R23 is a C1-C6 alkyl group; R24 is a C1-C6 alkyl group; R25 is a C1-C6 alkyl group; R26 is a C1-C6 alkyl group; R27 is a C1-C6 alkyl group; R28 is a C1-C6 alkyl group; R29 is a C1-C6 alkyl group; R30 is a C1-C6 alkyl group; R31 is a C1-C6 alkyl group; R32 is a C1-C6 alkyl group; R33 is a C1-C6 alkyl group; R34 is a C1-C6 alkyl group; R35 is a C1-C6 alkyl group; R36 is a C1-C6 alkyl group; R37 is a C1-C6 alkyl group; R38 is a C1-C6 alkyl group; R39 is a C1-C6 alkyl group; R40 is a C1-C6 alkyl group; R41 is a C1-C6 alkyl group; R42 is a C1-C6 alkyl group; R43 is a C1-C6 alkyl group; R44 is a C1-C6 alkyl group; R45 is a C1-C6 alkyl group; R46 is a C1-C6 alkyl group; R47 is a C1-C6 alkyl group; R48 is a C1-C6 alkyl group; R49 is a C1-C6 alkyl group; R50 is a C1-C6 alkyl group; R51 is a C1-C6 alkyl group; R52 is a C1-C6 alkyl group; R53 is a C1-C6 alkyl group; R54 is a C1-C6 alkyl group; R55 is a C1-C6 alkyl group; R56 is a C1-C6 alkyl group; R57 is a C1-C6 alkyl group; R58 is a C1-C6 alkyl group; R59 is a C1-C6 alkyl group; R60 is a C1-C6 alkyl group; R61 is a C1-C6 alkyl group; R62 is a C1-C6 alkyl group; R63 is a C1-C6 alkyl group; R64 is a C1-C6 alkyl group; R65 is a C1-C6 alkyl group; R66 is a C1-C6 alkyl group; R67 is a C1-C6 alkyl group; R68 is a C1-C6 alkyl group; R69 is a C1-C6 alkyl group; R70 is a C1-C6 alkyl group; R71 is a C1-C6 alkyl group; R72 is a C1-C6 alkyl group; R73 is a C1-C6 alkyl group; R74 is a C1-C6 alkyl group; R75 is a C1-C6 alkyl group; R76 is a C1-C6 alkyl group; R77 is a C1-C6 alkyl group; R78 is a C1-C6 alkyl group; R79 is a C1-C6 alkyl group; R80 is a C1-C6 alkyl group; R81 is a C1-C6 alkyl group; R82 is a C1-C6 alkyl group; R83 is a C1-C6 alkyl group; R84 is a C1-C6 alkyl group; R85 is a C1-C6 alkyl group; R86 is a C1-C6 alkyl group; R87 is a C1-C6 alkyl group; R88 is a C1-C6 alkyl group; R89 is a C1-C6 alkyl group; R90 is a C1-C6 alkyl group; R91 is a C1-C6 alkyl group; R92 is a C1-C6 alkyl group; R93 is a C1-C6 alkyl group; R94 is a C1-C6 alkyl group; R95 is a C1-C6 alkyl group; R96 is a C1-C6 alkyl group; R97 is a C1-C6 alkyl group; R98 is a C1-C6 alkyl group; R99 is a C1-C6 alkyl group; R100 is a C1-C6 alkyl group; R101 is a C1-C6 alkyl group; R102 is a C1-C6 alkyl group; R103 is a C1-C6 alkyl group; R104 is a C1-C6 alkyl group; R105 is a C1-C6 alkyl group; R106 is a C1-C6 alkyl group; R107 is a C1-C6 alkyl group; R108 is a C1-C6 alkyl group; R109 is a C1-C6 alkyl group; R110 is a C1-C6 alkyl group; R111 is a C1-C6 alkyl group; R112 is a C1-C6 alkyl group; R113 is a C1-C6 alkyl group; R114 is a C1-C6 alkyl group; R115 is a C1-C6 alkyl group; R116 is a C1-C6 alkyl group; R117 is a C1-C6 alkyl group; R118 is a C1-C6 alkyl group; R119 is a C1-C6 alkyl group; R120 is a C1-C6 alkyl group; R121 is a C1-C6 alkyl group; R122 is a C1-C6 alkyl group; R123 is a C1-C6 alkyl group; R124 is a C1-C6 alkyl group; R125 is a C1-C6 alkyl group; R126 is a C1-C6 alkyl group; R127 is a C1-C6 alkyl group; R128 is a C1-C6 alkyl group; R129 is a C1-C6 alkyl group; R130 is a C1-C6 alkyl group; R131 is a C1-C6 alkyl group; R132 is a C1-C6 alkyl group; R133 is a C1-C6 alkyl group; R134 is a C1-C6 alkyl group; R135 is a C1-C6 alkyl group; R136 is a C1-C6 alkyl group; R137 is a C1-C6 alkyl group; R138 is a C1-C6 alkyl group; R139 is a C1-C6 alkyl group; R140 is a C1-C6 alkyl group; R141 is a C1-C6 alkyl group; R142 is a C1-C6 alkyl group; R143 is a C1-C6 alkyl group; R144 is a C1-C6 alkyl group; R145 is a C1-C6 alkyl group; R146 is a C1-C6 alkyl group; R147 is a C1-C6 alkyl group; R148 is a C1-C6 alkyl group; R149 is a C1-C6 alkyl group; R150 is a C1-C6 alkyl group; R151 is a C1-C6 alkyl group; R152 is a C1-C6 alkyl group; R153 is a C1-C6 alkyl group; R154 is a C1-C6 alkyl group; R155 is a C1-C6 alkyl group; R156 is a C1-C6 alkyl group; R157 is a C1-C6 alkyl group; R158 is a C1-C6 alkyl group; R159 is a C1-C6 alkyl group; R160 is a C1-C6 alkyl group; R161 is a C1-C6 alkyl group; R162 is a C1-C6 alkyl group; R163 is a C1-C6 alkyl group; R164 is a C1-C6 alkyl group; R165 is a C1-C6 alkyl group; R166 is a C1-C6 alkyl group; R167 is a C1-C6 alkyl group; R168 is a C1-C6 alkyl group; R169 ​ R is -(CH2) m CH3or -(CH2) n SO3 - M + , m = 0, 1 or 2, n = 2, 3 or 4, M + is Na + or H + .

2. The process for the preparation of N-alkylated / sulfonated benzimidazole functionalized bisphenol monomers as claimed in claim 1, wherein, ​ ​ ​ ​ ​ ​ 3. The production method according to claim 2, wherein ​ 4. The production method according to claim 2, wherein ​ 5. The production method according to claim 2, wherein ​ 6. A N-alkylated / sulfonated benzimidazole poly(arylene ether ketone / sulfone) with controllable grafting density, characterized in that, ​ ​ ​ ​ ​ 7. The graft density controllable N-alkylated / sulfonated benzimidazole poly( aryl ether ketone / sulfone) of claim 6, wherein, ​ 8. The graft density controllable N-alkylated / sulfonated benzimidazole poly (aryl ether ketone / sulfone) of claim 6, wherein, ​ ​ ​